Robust method for determining the orbits of geostationary satellites with a lack of data - Demchenko, B.I.; Komarov, A.A.; Ussoltseva, L.A. (Recent Contributions to Physics, 2016)
The algorithm determining the Keplerian orbit elements GSS is presented taking into account a priori information. For it is proposed to use a regular system of elements Ei (i = 1, ..., 6). It is support system, free from that famous mathematical uncertainty elements of Kepler, which is associated with their non-orthogonality. Elements of the proposed support system are calculated by iterative method of differential corrections. In this case it is possible to consider a priori limitations and increase the stability of the algorithm.